Non-del(5q) myelodysplastic syndromes-associated loci detected by SNP-array genome-wide association meta-analysis - McGraw, KL; Cheng, C-H; Chen, YA; Hou, H-A; Nilsson, B; Genovese, G; Cluzeau, T; Pellagatti, A; Przychodzen, BP; Mallo, M; Arenillas, L; Mohamedali, A; et al. (American Society for Hematology, 2019)
Myelodysplastic syndromes (MDS) are hematopoietic stem cell malignancies. Known predisposing factors to adult MDS include rare germline mutations, cytotoxic therapy, age-related clonal hematopoiesis, and autoimmune or chronic inflammatory disorders. To date, no published studies characterizing MDS-associated germline susceptibility polymorphisms exist. We performed a genome-wide association study of 2 sample sets (555 MDS cases vs 2964 control subjects; 352 MDS cases vs 2640 control subjects) in non-del(5q) MDS cases of European genomic ancestry. Meta-analysis identified 8 MDS-associated loci at 1q31.1 (PLA2G4A), 3p14.1 (FAM19A4), 5q21.3 (EFNA5), 6p21.33, 10q23.1 (GRID1), 12q24.32, 15q26.1, and 20q13.12 (EYA2) that approached genome-wide significance. Gene expression for 5 loci that mapped within or near genes was significantly upregulated in MDS bone marrow cells compared with those of control subjects (P < .01). Higher PLA2G4A expression and lower EYA2 expression were associated with poorer overall survival (P = .039 and P = .037, respectively). Higher PLA2G4A expression is associated with mutations in NRAS (P < .001), RUNX1 (P = .012), ASXL1 (P = .007), and EZH2 (P = .038), all of which are known to contribute to MDS development. EYA2 expression was an independently favorable risk factor irrespective of age, sex, and Revised International Scoring System score (relative risk, 0.67; P = .048). Notably, these genes have regulatory roles in innate immunity, a critical driver of MDS pathogenesis. EYA2 overexpression induced innate immune activation, whereas EYA2 inhibition restored colony-forming potential in primary MDS cells indicative of hematopoietic restoration and possible clinical relevance. In conclusion, among 8 suggestive MDS-associated loci, 5 map to genes upregulated in MDS with functional roles in innate immunity and potential biological relevance to MDS.